How to treat subsyndromal anxiety disorder - practical recommendations for implementation in primary care - Costa, Daniel Lucas da Conceição; Furlan Damiano, Rodolfo; Alcalá, José Ángel; Hatzinger, Martin; Mesa, Francisco; Perna, Giampaolo; Purebl, György; Torzsa, Péter; Vobořilová, Věra; Zwanzger, Peter; Ho, Roger; Bandelow, Borwin (International journal of psychiatry in clinical practice, 2024)
BACKGROUND: Anxiety is a common and disabling condition that significantly impacts quality of life. Subsyndromal anxiety (SSA) refers to anxiety symptoms that do not meet the full diagnostic criteria for an anxiety disorder but pose a risk for developing such disorders. We aimed to provide practical recommendations for the treatment of SSA in primary care settings. METHODS: A narrative review was conducted to identify strategies for recognizing and treating patients with SSA. RESULTS: The recommendations for treating SSA include lifestyle modifications such as exercise and stress reduction techniques, psychotherapy, and pharmacological treatments, including natural compounds like the lavender oil extract Silexan. Regular follow-up care is essential to monitor treatment response and address ongoing symptoms. Additionally, the use of the GAD-7 tool is recommended for accurately identifying patients with SSA. CONCLUSION: Implementing these recommendations in primary care can lead to effective treatment of SSA, preventing the development of more severe anxiety disorders. An integrative approach, combining lifestyle modifications, psychotherapy, and pharmacotherapy, including natural compounds, offers significant benefits for managing anxiety.
Keywords: family medicine; community psychiatry; general practitioner; úzkostné poruchy; primární zdravotní péče; Humans; Anxiety Disorders; Psychotherapy; Anxiety disorders; primary care; subsyndromal anxiety; Primary Health Care; psychoterapie; lidé